General consensus on multimodal functions and validation analysis of perinatal derivatives for regenerative medicine applications - Pozzobon, Michela; D’Agostino, Stefania; Roubelakis, Maria G.; Cargnoni, Anna; Gramignoli, Roberto; Wolbank, Susanne; Gindraux, Florelle; Bollini, Sveva; Kerdjoudj, Halima; Fenelon, Mathilde; Di Pietro, Roberta; Basile, Mariangela; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Perinatal tissues, such as placenta and umbilical cord contain a variety of somatic stem cell types, spanning from the largely used hematopoietic stem and progenitor cells to the most recent described broadly multipotent epithelial and stromal cells. As perinatal derivatives (PnD), several of these cell types and related products provide an interesting regenerative potential for a variety of diseases. Within COST SPRINT Action, we continue our review series, revising and summarizing the modalities of action and proposed medical approaches using PnD products: cells, secretome, extracellular vesicles and decellularized tissues. Focusing on brain, bone, skeletal muscle, heart, intestinal, liver and lung pathologies, we discuss the importance of potency testing in validating PnD therapeutics, as well as and critically evaluate the concept of PnD application in the field of tissue regeneration. Hereby we aim to shed light on the actual therapeutic properties of PnD, with an open eye for future clinical application. This review is part of a quadrinomial series on functional assays for validation of PnD, spanning biological functions, such as immunomodulation, anti-microbial/anti-cancer, anti-inflammation, wound healing, angiogenesis, and regeneration.